Effects of Oxycodone on Sensitivity to Reinforcement Magnitude: Implications for Effects of Opioids on Impulsive and Risky Choice - Hunt, Katelyn H. (Behav Pharmacol, 2020)
Opioid addition/dependence is associated with impulsive and risky behavior. Moreover, opioids can increase impulsive choice in pre-clinical studies with non-humans. The objective of this study was to investigate a potential behavioral mechanism of opioids: a change in the impact of reinforcement magnitude on choice. Rats (n=7) chose between smaller and larger reinforcers under a continuous-choice (concurrent-chains) procedure. The levers associated with the smaller and larger reinforcers alternated every five sessions. During baseline under this procedure, rats showed a reliable preference for the larger reinforcer. Effects of several doses (0.1-1.7 mg/kg, s.c.) of the prescription opioid, oxycodone, were examined on preference based upon reinforcement magnitude. Oxycodone dose-dependently decreased preference for the larger reinforcer (i.e., decreased sensitivity to reinforcement magnitude). The decrease in sensitivity to reinforcement magnitude was selective in that the intermediate doses did not affect, or had minimal impact on, other measures of performance (e.g., on general motivation to respond). These data suggest that a decrease in the sensitivity to reinforcement magnitude is a reliable outcome of μ-opioid administration, an effect that has important implications for the impact of these drugs on both impulsive and risky behavior.